The Theatre Organised by the Industrial and Handicraft Youth Association in Krakow – Inspired by Father Mieczysław Kuznowicz, a Graduate of the Jesuit School in Chyrów - Małgorzata Puchowska (Horyzonty Wychowania, 2015)
The theatre established by the Industrial and Handicraft Youth Association is a representative of the amateur theatre movement, typical for Krakow during the inter-war period. However, it has one remarkable feature – it was created by young people from very diverse social backgrounds, far from the gymnasium elite, often illiterate. They were connected by common passion and artistic needs, awakened by the creative educational concept of Father Mieczysław Kuznowicz. The aim of the theatre on Skarbowa Street was to use appropriate dramatic texts to develop religious, national and social feelings among the members of the association, to teach proper communication in the mother tongue and to form the habits of cultural behaviour and solid teamwork. The form of the youth theatre adopted in the association seems to correspond with the concept known from the theatrical stages of Jesuit schools. The author attempts to answer the following question: ”To what extent did the experiences of Kuznowicz, a graduate of the Scientific and Educational Department of the Jesuits in Chyrów, influence the shape of the theatrical stage in Krakow?”